Metaverse technological adoption: A study of processes, behaviors and attitudes - Serras, C.; Alturas, B.; Lapa, T. (Metaverse driven intelligent information systems: Emerging trends and future directions, 2024)
The way we connect to the world around has undergone profound changes due to technological innovations. While these innovations have enabled greater access to information, instant communication, and opportunities for creativity, they have also given rise to issues related to health, privacy, and social isolation. The Metaverse emerges as an ambitious promise to create a virtual world in which individuals from all over the world can interact in a more immersive manner than ever before, often referred to as the future of the Internet. As technology becomes increasingly intertwined into daily lives, it becomes essential to understand the perceptions and attitudes towards these technological advances. This article aims to comprehend individuals’ perceptions of current technology and its usage, as well as their perception of the creation of a truly immersive virtual world like the Metaverse. It also encompasses a literature review of the most pertinent traits of the Metaverse, formulated hypotheses based on an adapted Technology Acceptance Model (TAM), and data analysis based on an online questionnaire. The data collected was analysed using SPSS software, with the goal of capturing the current perspectives regarding the Metaverse and technological use in general. This study aspires to contribute to current research on technological adoption and perception and to offer deeper insights into the possible social impacts of technological advancements.